ELECTIVIST: a novel system to improve elective caesarean section booking. Issue 3 (29th August 2018) - Robertson, Katherine; Clacey, Joe; D'Arcy, Rhiannon; Khan, Neveen; Reddy, Aparna
Abstract : Elective caesarean sections (ELCS) vary widely in surgical complexity and are routinely performed between 39 and 40 weeks of pregnancy. Unselected ELCS lists may create clinical risk due to inappropriately complex case mixes and over-running theatre time, impacting on emergency care. Despite evidence that ELCS list over-run is a widespread concern for many units, there is a paucity of literature regarding effective ELCS booking systems. We designed a novel ELCS risk scoring system, ELECTIVIST, comprising a risk assessment by the booking clinician and allocation of a complexity score to each case from 1 to 6. The maximum risk score for any one patient was 6, with a maximum total score on any one ELCS list of 6 and a maximum of three cases per list. We performed a retrospective analysis of all ELCS performed in our unit in 2016 using existing booking information and theatre data to assess existing case mix complexity and theatre over-run. This showed that 36% of ELCS lists were overbooked with inappropriately complex case mix and 21% of lists over-ran with 6% impacting on emergency obstetric theatres. Assessment of the impact of ELECTIVIST on ELCS capacity prior to implementation showed that no additional capacity was required to accommodate existing complexity. At 6 months following implementation, theatre over-run was reduced to 10% and over-run impacting on emergency theatre to 1%. The requirement for extra ELCS lists to accommodate capacity reduced by 66%. ELECTIVIST is a novel system that improves ELCS booking using existing capacity and reduces theatre list over-run. It is transferable, cost neutral and could be widely applied in obstetric units.